ANALISIS KEUANGAN DAN TARIF PAJAK PADA CV HARKAT ABADI TIMIKA - Ahmad Riadin; Muhammad Sabir (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2018)
The aims of the research to determine the financial condition of CV Harkat Abadi Timika using liquidity ratios, solvency ratios, and profitability ratios as well as the amount of corporate income tax rates imposed. Data is collected using documentation techniques. In this technique, data is obtained directly from CV Harkat Abadi Timika in the form of financial statements for 2016-2016. To find out the level of liquidity of CV Harkat Abadi Timika is measured using liquidity ratios. Solvency ratio is used to measure the company's ability to pay off its long-term debt. To determine the company's ability to generate profits, profitability ratios are used. The amount of PP 46 tax is obtained from total gross income multiplied by 1%. The results of the analysis show that: (1) CV. Harkat Abadi Timika's liquidity is good because the ratio is above the industry average and has increased. (2) Solvability is good because it has decreased every period. (3) Profitability is classified as good and has increased. This means that there is an increase in the company's ability to generate profits